Total and Double Total Domination Number on Hexagonal Grid - Antoaneta Klobučar (Mathematics, 2019)
In this paper, we determine the upper and lower bound for the total domination number and exact values and the upper bound for the double-total domination number on hexagonal grid <semantics> H m , n </semantics> with m hexagons in a row and n hexagons in a column. Further, we explore the ratio between the total domination number and the number of vertices of <semantics> H m , n </semantics> when m and n tend to infinity.